Performance Evaluation of BPEL4People Specifications Integrate Human Interactions Into Business Process - Holanda, Henrique Jorge; Merseguer, José Javier; Barroso, Giovanni Cordeiro; Serra, A. B. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2010: Anais do VI Simpósio Brasileiro de Sistemas de Informação, 2010)
WS-BPEL Extension for People (BPEL4People) introduces human activity to Web Services Business Process Execution Language (WS-BPEL/BPEL). Some works have been done on the performance verification of WS-BPEL, but there aren't works on the performance verification of WS-BPEL4People. In this paper, we propose a model method for the transformation of WS-BPEL4People/BPEL4People into Generalized Stochastic Petri Nets (GSPN) and this way evaluate its performance. During the transformation, Petri Net is used to model BPEL activities and the human activity of a human task. Then, by validating the generated model, some potential problems with performance of WS-BPEL4People can be detected.